Pengaruh Faktor Pendorong Dan Tambatan Terhadap Niat Beralih Produk Reglow - Yanti Yanti; Anna Zakiyah Hastriana (Jurnal Pendidikan Indonesia (JOUPI), 2024)
The needs of Indonesians are driving a rapid development in beauty products, particularly in skincare. Reglow is one of those products that Indonesians truly appreciate, as evidenced by the sales process, which has prompted competition among cosmetic companies for the attention of consumers. The aim of this research is to examine and evaluate the influence of consumer dissatisfaction and low product quality as motivators for product switching intentions, as well as the influence of knowledge value as a stabilizing factor on switching intentions for repeat purchases. The decision of a customer to switch is influenced by a variety of factors. This research employs a quantitative methodology. In this study, primary data were used as the data source. A Likert scale questionnaire was used to collect the data. Purposive sampling was used to select 95 respondents for the Santriwati Ppondok Pesantren Annuqayah Lubangasa Putri sample for this study. The data in this study will then be analyzed using multiple linear regression in SPSS 21 for Windows. The study's findings indicate that while knowledge value has a negative impact on consumers' intentions to switch to skincare reglow products, customer dissatisfaction and poor product quality have a positive influence.